Pushing the Limits of Child Participation in Research: Reflections from a Youth-Driven Participatory Action Research (YPAR) Initiative in Uganda. (22nd October 2020) - Ritterbusch, Amy E.; Boothby, Neil; Mugumya, Firminus; Wanican, Joyce; Bangirana, Clare; Nyende, Noah; Ampumuza, Doreen; Apota, John; Mbabazi, Cate; Nabukenya, Christine; Kayongo, Adam; Ssembatya, Fred; et al.
Background: Violence against children (VAC) in Uganda is recognized as an urgent dilemma; however, most research has been quantitatively oriented and has seldom involved children in the research process. Objective: We discuss what we learned about child participation in the research process as a means of informing ethical praxis in future child- and youth-led research initiatives. As an overarching aim of this paper, we utilize our engagement with YPAR as a springboard to reflect on methodological best practices for VAC research that involve children themselves as part of a movement to democratize the research process. Participants and Setting: The study includes street-connected children (40), sexually exploited children (19) and domestic workers (34) in Kampala. Methods: The YPAR team led participant observation, 52 semi-structured life history interviews, 31 auto-photographic exercises, and 4 focus groups. All data collection, analysis and dissemination activities were led by the YPAR team including four Ugandan street-connected youth between the ages of 16–25 and two Ugandan university-trained youth researchers. Results: The results are framed as a methodological reflection regarding the complexities and transformative potential of including children as researchers in the framework of YPAR. Conclusions: We urge scholars to create spaces for sustainable YPAR movements, both in academic and policy arenas, and to design participatory initiatives that prioritize knowledge produced by and for the improvement of children's lives globally. We encourage challenging traditional, extractive research practices through participatory approaches that carve out spaces for child participation in research.